Simulation Model and Genetic Algorithm to Assembly Line Balancing - Ali, A. J. Adham; Ahmad Nazif, Noor Kamar; Abdullah, Ibrahim; Sorooshian, Shahryar (Universiti Malaysia Pahang, 2013)
Assembly lines are flow-line production systems which are of great importance in the industrial production of high quantity standardized commodities and more recently even gained importance in low volume production of customized products. The assembly line involves many famous problems that is unbalancing cycle time among the workstations. Simulation Model (SM) is one of the most useful modelling tool for the design of many types of systems. It can combine with Genetic Algorithm system (GAs) to obtain the optimum solution in any type of issue area. In this study the SM and GAs will be applied to solve the unbalancing problem at the automobile manufacture system. This method will improve the efficiency of the assembly line through reduces the queuing among the workstation, increase the labor of working time then to increase the ratio of the productions.